(untitled) (Journal of Atomic and Molecular Sciences, 2017)
In this paper, we investigate the double ionization process of He for the shakeoff (SO) and correlated energy-sharing (CES) channels in intense laser field based on the intense-field many body S-matrix theory (IMST). The wavelength dependence of the ionization rate from these two channels are analyzed and compared with each other. According to our calculation, the CES channel dominants at long wavelengths (300-780nm), while the SO channel dominants at short wavelengths (20-200nm). The more interesting thing occurs in the intermediate wavelength regime (200-300nm) where the contributions from the SO and CES channels are comparable and may compete with each other.